(untitled) (Reinforce: Journal of Sharia Management, 2025)
The background of this research is by UMKM which are developing very rapidly, especially in the culinary sector. Business actors must be able to adapt to current developments and innovate in order to attract consumers so that their business is able to survive the threat of competitors, is able to take advantage of existing opportunities, and continues to develop amidst increasingly fierce business competition. The purpose of this research is to find out the influence of packaging, product variations and electronic word of mouth (E-WOM) on consumer buying interest at Raja Nyemil Tulungagung partially and simultaneously. The sample taken in the research was 68 respondents from Raja Nyemil Tulungagung consumers. A quantitative approach is used in this research and is an associative type of research. Using primary data, the data collection method is a questionnaire with a Likert scale. The analytical method used is the multiple linear regression test using the SPSS 16.0 application. The results of this research show that partially and simultaneously significant results were obtained which means that there is a positive and significant influence between packaging, product variety and Electronic Word of Mouth (E-WOM) on consumer buying interest in Raja Nyemil Tulungagung.